2008
DOI: 10.1243/09544119jeim476
|View full text |Cite
|
Sign up to set email alerts
|

Load- and displacement-controlled finite element analyses on fusion and non-fusion spinal implants

Abstract: This study used finite element (FE) analysis with the load-controlled method (LCM) and the displacement-controlled method (DCM) to examine motion differences at the implant level and adjacent levels between fusion and non-fusion implants. A validated three-dimensional intact (INT) L1-L5 FE model was used. At the L3-L4 level, the INT model was modified to surgery models, including the artificial disc replacement (ADR) of ProDisc II, and the anterior lumbar interbody fusion (ALIF) cage with pedicle screw fixatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 44 publications
6
60
1
Order By: Relevance
“…For the adjacent levels, the present study revealed that the ROM increased by at least 22.4% in flexion and 15.6% in lateral bending; these trends conflict with the findings of some in vitro tests under the load control method [9,21]. Our earlier study demonstrated that the effects on adjacent levels are more prominent under the displacement control method after insertion of a spinal implant when compared with the load control method [18]. This conflicting result can be explained by the use of different testing protocols in the present FE simulation and previous in vitro tests.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…For the adjacent levels, the present study revealed that the ROM increased by at least 22.4% in flexion and 15.6% in lateral bending; these trends conflict with the findings of some in vitro tests under the load control method [9,21]. Our earlier study demonstrated that the effects on adjacent levels are more prominent under the displacement control method after insertion of a spinal implant when compared with the load control method [18]. This conflicting result can be explained by the use of different testing protocols in the present FE simulation and previous in vitro tests.…”
Section: Discussioncontrasting
confidence: 94%
“…First, ROMs in five levels of the INT model under different moments of 3.75, 7.5, and 10 Nm were validated with the results of the previous study [18]. Good agreement of ROMs was achieved under most of the loading cases.…”
Section: Convergence Test and Model Validationmentioning
confidence: 76%
See 3 more Smart Citations